Pengaruh Substitusi Cangkang Kerang Darah dan Fly Ash Terhadap Campuran Perkerasan Aspal - maulida, siti mira; Suhendra, Tobi; Darma, Yusria; M Saleh, Sofyan; Dasopang, Ahyin Bilhuda; Mauladea, Faiza; Humayra, S (Universitas Iskandar Muda, 2025)
Research on asphalt mixtures continues to progress through sustainable innovations, particularly in the utilization of waste materials as substitution components. The incorporation of such waste not only helps mitigate environmental but also contributes to improving the mechanical performance of asphalt mixtures. One promising waste material is Blood Cockle Shell (BCS), a by-product of fishery activities that has not yet been fully utilized. In this study, BCS was used as a substitution for fine aggregates in asphalt concrete mixtures, while fly ash was utilized as a filler substitute at a constant proportion of 5%. The main objective of this research was to analyze the effect of CKD content variations of 0%, 10%, and 15% on the Marshall characteristics and durability. The experimental procedure involved conducting Marshall tests on 27 specimens, with the Optimum Asphalt Content (OAC) determined at 5.91%. The results showed that all BCS variations met the Bina Marga (2020) specifications. The best performance was achieved at 10% BCS content, demonstrating high stability, flow within the middle range, and a durability value of 94.07%, exceeding the minimum requirement of 90%. These results suggest that BCS combined with fly ash provides an environmentally sustainable alternative material for improving pavement quality.